Recurrent thrombotic occlusions of arteries and veins caused by intravascular metastatic adenocarcinoma. Issue 9 (September 1994) - Levi, M; Bronkhorst, C; Noorduyn, L A; Vreeken, J
Abstract : The occurrence of unexplained, rapidly recurring occlusions of arteries and veins in a previously healthy young woman is described. Post mortem examination showed no macroscopic abnormalities but revealed microscopic metastatic adenocarcinoma with remarkable intravascular localisation of the malignant cells. Whereas highly sensitive markers for the existence of systemic activation of blood coagulation remained within the normal range, it is suggested that specific characteristics of the tumour cells may have been responsible for this particular clinical presentation.